Supply Chain Planning - Liberatore, Matthew J (Business Expert Press, 2012)
Ebook from IG Library ; In today's competitive global economy, a firm's market position and bottom-line financial performance is closely linked to its supply chain performance. All too often considerable managerial resources are directed toward planning activities and processes with little in the way of tangible results and outcomes. What supply chain executives require is the knowhow to efficiently and effectively direct their planning activities so that the results lead to better business decisions from the long-term down to day-to-day operations. In this book, we present proven, practical management frameworks and techniques used by the authors to support supply chain operations management and planning in private industry. These frameworks describe supply chain strategic planning and project selection techniques, integrated manufacturing-distribution planning and scheduling approaches, performance measurement and balanced scorecard methodologies, customer logistics and inventory deployment decision support systems, and other well-tested management frameworks.